Theoretical Analysis on Distribution Pattern of Plastic Zone in Surrounding Rock of High-Gas-Coal Roadway - Chao Yuan; Liming Cao; Lei Fan; Jianqiang Guo (Advances in Civil Engineering)
The formation and expansion of the plastic zone is always accompanied by the deformation and failure of the roadway-surrounding rock. Based on elastoplastic theory, this paper considers the gas pressure parameters and uses the Mohr–Coulomb strength criterion to derive the implicit equation of the plastic zone boundary in the rock surrounding gas-coal roadways. The distribution characteristics of the plastic zone of gas-coal roadway-surrounding rock are studied, and the sensitivity to the gas pressure, cohesion, internal friction angle, and support strength of the roadway free face on the plastic zone of the surrounding rock is analyzed. The research results show that the plastic zone of the surrounding rock has four distribution patterns: circular, elliptical, rounded rectangle, and butterfly. Additionally, the lateral pressure coefficient, gas pressure, cohesion, and internal friction angle are found to jointly determine the distribution and range of the plastic zone. However, the support strength of the roadway free face does not change the distribution of the plastic zone but only affects its range. The circular and elliptical plastic zones are less sensitive to gas pressure, cohesion, and internal friction angle, whereas butterfly-shaped plastic zones are highly sensitive to these factors. The main manifestation of this sensitivity is that the four butterfly leaves degenerate rapidly with any decrease in the gas pressure or increase in the cohesion and internal friction angle. Larger butterfly leaves are prone to faster degeneration. The research results presented in this paper have important theoretical guiding significance and engineering application value for the design of high-gas-coal roadway support and gas drilling.